NASIONALISME SEBAGAI KONSTRUKSI POLITIK DALAM TEKS MEDIA DI INDONESIA KAITAN DENGAN ETIKA MEDIA - Ikasari, Prinisia Nurul (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2015)
Abstract :Political imagery in the media is closely related to the media construction. Two of the television media Metro TV and Tv One whose owner is affiliated with political world emerged as of partisan one presidential candidate. Many Ways That is done in the political construction news, one as feared Injurious independence day celebrations in Indoenesia. This research aimed to expose the construction of the text by the two media during the celebration of Independence Day of the Republic of Indonesia to 69 and linking with existing media ethics in Indonesia. This study uses a semiotic analysis of Roland Barthes. Results showed that there was an attempt constructs images taken by both media Metro TV and Tv One, to the procession of Indonesian Independence Day celebrations, which indicated the existence of abuse of power in the media and media ethics violations.